Peran pendidikan multikultural dalam mempersiapkan siswa untuk dunia global - Utami, Lukas Sri (Maliki Interdisciplinary Journal, 2025)
Multicultural education plays a crucial role in preparing students for an increasingly connected globalised world. In the era of globalisation, the ability to appreciate cultural diversity, communicate across cultures, and have critical thinking and empathy are essential. This article discusses the role of multicultural education in shaping young people who are ready to face global challenges. Through an inclusive approach, it reduces prejudice, strengthens cross-cultural communication and develops tolerance among students. However, the implementation of multicultural education faces challenges such as community resistance, curriculum limitations and lack of teacher training. Solutions to these challenges include more intensive socialisation to parents, curriculum revisions that include cross-cultural material and continuous teacher training programmes. Experiential learning and the use of technology are also important tools to enrich students' understanding of cultural diversity. With these measures, multicultural education can create a generation that is more adaptive, tolerant and ready to contribute to an increasingly complex global society.